Exploring recent patterns of migration of doctors to the United Kingdom: a mixed-methods study - N. Brennan; N. Langdon; T. Gale; N. Humphries; A. Knapton; M. Bryce (BMC, 2023)
Abstract Introduction A shortage of doctors is currently one of the biggest challenges faced by the healthcare workforce in the United Kingdom (UK). While plans are in place to increase the number of medical school places, in the short-term this gap will need to continue to be filled by the international recruitment of doctors. The aim of this study is to identify key factors that explain the patterns of migration of doctors to the UK, in order to aid the development of policies to recruit and retain a sustainable workforce. Methods We analysed General Medical Council (GMC) secondary data on the patterns of migration of internationally trained doctors (2009-2019). Qualitative interviews were conducted with 17 stakeholders by videoconferencing which were audio-recorded, transcribed and thematically analysed using NVivo. Results In 2019, 34.5% of UK doctors were trained internationally mainly in India, Pakistan, Italy, Nigeria, Greece, Romania and Egypt. Most new registrations by internationally trained doctors from 2009-2019 did not have a specialty at the time of initial registration (96.2% in 2019). Only a relatively small number of these doctors go on to gain specialist or GP registration (11.6% within 5 years and 27.2% within 10 years of registration). The stakeholder interviews highlighted training opportunities and career progression as the main drivers of migration. The barriers internationally trained doctors face regarding specialty training included differences between UK and destination health systems, systematic bias, bureaucracy and selection processes not being accessible. Conclusion This study makes a contribution to the literature by identifying recent patterns in the migration of doctors to the UK. The UK's dependence on internationally trained doctors has important global implications as source countries are losing skilled health workers which is undermining their health systems. In keeping with the WHO Global Code on the International Recruitment of Healthcare Personnel, policymakers need to consider how to reduce the UK's reliance on internationally trained doctors, particularly from countries on the safeguard list whilst continuing the drive to increase medical school places. Additional support is required for internationally trained doctors, to ensure that they get on the training programmes they seek, enabling their career progression.